Pharmacological basis for the medicinal use of Rhus coriaria in hyperactive gut disorders - Khalid Hussain Janbaz; Arham Shabbir; Malik Hassan Mehmood; Anwarul Hassan Gilani (Bangladesh Pharmacological Society, 2014)
This study was aimed at providing the pharmacological basis for the medicinal use of Rhus coriaria in diarrhea. In mice, the crude of R. coriaria demonstrated antisecretory and antidiarrheal effects against castor oil-induced fluid accumulation and diarrhea at at 100 and 300 mg/kg, respectively, and was found safe up to tested dose of 5 g/kg. In isolated rabbit jejunum, R. coriaria exhibited concentration-dependent (0.01-3.0 mg/mL) relaxation of spontaneous and high K+ (80 mM)-induced contractions, similar to verapamil. The Ca++ antagonist activity was confirmed when pretreatment of R. coriaria shifted Ca++ concentration-response curves to the right with suppression of maximal response, similar to verapamil. R. coriaria also suppressed the high K+-evoked transient contractile peaks similar to the effect of cyclopiazonic acid and verapamil. This study indicates that R. coriaria possesses antisecretory, antidiarrheal and antispasmodic properties mediated possibly through Ca++ antagonist pathway, thus providing evidence to its medicinal use in diarrhea and abdominal spasm. DOI: http://dx.doi.org/10.3329/bjp.v9i4.20879